Neuronal-specific methylome and hydroxymethylome analysis reveal significant loci associated with alcohol use disorder - Andrade-Brito, Diego E.; Núñez-Ríos, Diana L.; Martínez-Magaña, José Jaime; Nagamatsu, Sheila T.; Rompala, Gregory; Zillich, Lea; Witt, Stephanie H.; Clark, Shaunna L.; Lattig, Maria C.; Montalvo-Ortiz, Janitza L.; Alvarez, Victor E.; Benedek, David; et al. (Frontiers in Genetics, 2024)
Alcohol use disorder (AUD) is a complex condition associated with adverse health consequences that affect millions of individuals worldwide. Epigenetic modifications, including DNA methylation (5mC), have been associated with AUD and other alcohol-related traits. Epigenome-wide association studies (EWAS) have identified differentially methylated genes associated with AUD in human peripheral and brain tissue. More recently, epigenetic studies of AUD have also evaluated DNA hydroxymethylation (5hmC) in the human brain. However, most of the epigenetic work in postmortem brain tissue has examined bulk tissue. In this study, we investigated neuronal-specific 5mC and 5hmC alterations at CpG sites associated with AUD in the human orbitofrontal cortex (OFC). Neuronal nuclei from the OFC were evaluated in 34 human postmortem brain samples (10 AUD, 24 non-AUD). Reduced representation oxidative bisulfite sequencing was used to assess 5mC and 5hmC at the genome-wide level. Differential 5mC and 5hmC were evaluated using the methylKit R package and significance was set at false discovery rate <0.05 and differential methylation >2. Functional enrichment analyses were performed and gene-level convergence was evaluated in an independent dataset that assessed 5mC and 5hmC of AUD in bulk cortical tissue. We identified 417 5mC and 363 5hmC significant differential CpG sites associated with AUD, with 59% in gene promoters. Some of the identified genes have been previously implicated in alcohol consumption, including SYK, DNMT3A for 5mC, GAD1, DLX1, DLX2, for 5hmC and GATA4 in both. Convergence with a previous AUD 5mC and 5hmC study was observed for 28 genes. We also identified 5 and 35 differential regions for 5mC and 5hmC, respectively. Lastly, GWAS enrichment analysis showed an association with AUD for differential 5mC genes. This study reveals neuronal-specific methylome and hydroxymethylome dysregulation associated with AUD, identifying both previously reported and potentially novel gene associations with AUD. Our findings provide new insights into the epigenomic dysregulation of AUD in the human brain.